The Role of Resonant Leadership, Workplace Friendship and Serving Culture in predicting Organizational Commitment: the Mediating Role of Compassion at Work - Ali, Riaz; Kashif, Muhammad (Review of Business Management, 2020)
Purpose – This study aims to empirically demonstrate the positive effects of resonant leadership, workplace friendship and serving culture on organizational commitment through a mediating role of compassion at work. Design/methodology/approach – The data are collected from 442 front line employees (FLEs) working in Pakistani healthcare organizations by employing a cross-sectional survey. The collected data are analysed through the structural equation modelling (SEM) technique, using SmartPLS 3.0. Findings – All the proposed relationships are statistically supported. We found that resonant leadership, serving culture and workplace friendship predict normative commitment among healthcare frontliners through a mediating role of compassion at work. The results demonstrate an excellent model fit, where all the direct as well as indirect hypotheses are supported by the data. Originality/value – The analysis of the positive effects of resonant leadership, workplace friendship and serving culture as a unified framework to predict organizational commitment via the mediating role of compassion in a healthcare setting is unique to this study.